Writing chemistry patents and intellectual property - Waller, Francis J. (Wiley, 2011)
"This book, based on a short course the author gives for the American Chemical Socitey, provides the necessary insights, strategies, and examples of how to write a patent so it is not rejected by the United States Patent and Trade Office (USPTO) or the patent does not have invalid claims"--